Hummingbird salamander - VanderMeer, Jeff (MCD, Farrar, Straus and Giroux, 2021)
"From Jeff VanderMeer, the author of Annihilation, comes a brilliant speculative thriller of dark conspiracy, endangered species, and the end of all things"--